2018
DOI: 10.1155/2018/2976957
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 a Major Player in Attenuation of Hepatic Ischemia‐Reperfusion Injury by Reducing ROS via Its Downstream Mediators: SOD2, CYP‐D, and HIF‐1α

Abstract: Reactive oxygen species (ROS) production in hepatic ischemia-reperfusion injury (IRI) is a complex process where multiple cellular and molecular pathways are involved. Few of those molecular pathways are under the direct influence of SIRT3 and its downstream mediators. SIRT3 plays a major role in the mechanism of IRI, and its activation has been shown to attenuate the deleterious effect of ROS during IRI via SOD2-, CYP-D-, and HIF-1α-mediated pathways. The objective of this review is to analyze the current kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 124 publications
(171 reference statements)
0
41
0
1
Order By: Relevance
“…SIRT3 exerts protective effects on mitochondria against oxidative stress. SIRT3 deacetylates the critical antioxidant enzyme manganese superoxide dismutase 2 (SOD2) at two different lysine sites to enhance its ROS-scavenging capability in mitochondrial matrix [ [123] , [124] , [125] ]. SIRT6 modifies the histones via deacetylation in the promoter regions of NF-κB–activated genes to further inhibit the proinflammatory response [ 126 ].…”
Section: Oxidative Stress and Epigenetic Modifications In Diabetic Rementioning
confidence: 99%
“…SIRT3 exerts protective effects on mitochondria against oxidative stress. SIRT3 deacetylates the critical antioxidant enzyme manganese superoxide dismutase 2 (SOD2) at two different lysine sites to enhance its ROS-scavenging capability in mitochondrial matrix [ [123] , [124] , [125] ]. SIRT6 modifies the histones via deacetylation in the promoter regions of NF-κB–activated genes to further inhibit the proinflammatory response [ 126 ].…”
Section: Oxidative Stress and Epigenetic Modifications In Diabetic Rementioning
confidence: 99%
“…18 Reactive oxygen species (ROS) are increased during HIRI and studies have demonstrated that ROS may induce various forms of insulin resistance. 19 The use of antioxidants is believed to represent an effective treatment for insulin resistance. 20,21 As a commonly used intravenous anesthetic, propofol has a strong antioxidant capacity, and may improve the antioxidant capacity of red blood cells and tissues in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found the PI3K/Akt pathway is associated with cardiomyocytes apoptosis induced by I/R [36,37]. Some investigation found that HIF-1α participated in I/R injury in multiple organs as a critical modulator [38,39]. Liu and his colleagues found that DMY decreased the apoptosis and necrosis by I/R treatment, and PI3K/Akt and HIF-1α plays a crucial role in protection during this process.…”
Section: Bioinformatic Analysis and Luciferase Assay In The Present Smentioning
confidence: 99%